OPERASI PERDAMAIAN BERKELANJUTAN PBB PASCA KONFLIK DI TIMOR LESTE TAHUN 1999-2006 - Flavianus D Melsasail (Universitas Kristen Satya Wacana, 2016)
In the history of UN peace operations, East Timor is one of the peace operations that are considered successful. The role played by the United Nations not only focus on peacemaking efforts with the mediator between Indonesia and Timor Leste freedom fighters, but also in peacekeeping and peacebuilding programs such as peacekeeping operations and the development of economic, political, social and cultural. It is worth noting that the success achieved was due to the revolutionary strategy to evolve the role of the United Nations which is associated in an ad hoc institution with the specific mandate of these institutions. The formation of an ad hoc institution that makes the implementation of the program becomes more focused. Politically, these institutions have managed to map the needs, plans and steps needed to create peace in East Timor. Indeed the success of the strategy process and the United Nations in East Timor could be a recommendation for a model United Nations peacekeeping operation in the world.Keywords: Peacekeeping, Peacebulding, East Timor, United Nations